Study of the Injured Persons and the Injury Pattern in Road Traffic Accident in Sana’a City, Yemen - Abdulhameed Ali Al-Thaifani; Nabil Ahmed Al-Rabeei; Abdulsalam Mohammed Dallak (Advances in Public Health)
Background. Fatal road traffic accidents constitute a significant public health problem. Aim. The aim of the study was to analyze road traffic accidents in Sana’a city, Yemen, during 2013–2015. Methods. The required information and data of accidents were collected, respectively, from police reported road accident statistics, Sana’a city. 11684 cases of road traffic accidents during period 2013–2015 were studied. Results. 840 people were killed and 9760 people were injured in RTAs during 2013–2015 in Sana’a city. The accident rates per 100000 of the population were 234.8 in 2013, 180.3 in 2014, and 92.2 in 2015. Mortality rates per 100000 of the population were 15.17 in 2013, 12.2 in 2014, and 8.9 in 2015. High speed was the single most important factor responsible for accidents, deaths, and injuries accounting for 38.1% of RTAs followed by drivers’ fault accounting for 18.9% of the total RTAs. The most common age group involved was ≥18 years. Males accounted for 83.1% of killed and injured persons. Most frequent victims of road traffic accidents were vehicles motor (48.9%) followed by pedestrians (38.1%). More than half of RTAs occurred on the straight road. Conclusion. RTAs are a major source of public health concern in Sana’a city, Yemen. Preventive measures to reduce the burden of mortality and morbidity due to road accidents should be introduced.